"You shall be in the future someone that is very powerful" : the experiences of students with HIV/AIDS in rural, post-conflict Uganda - Walsh, Shannon (2015)
The roll out of Anti-Retroviral Therapy across Sub-Saharan Africa has given rise to a new generation of adolescents that previously would not have survived into their teen years. The aim of this research is to give voice to these young people, specifically HIV positive students, in the rural, post-conflict area of Katakwi, Uganda. Through the lens of empowerment, which focuses on participation, capacity building, leadership potential, and relationships, this research examines the factors in these students’ lives that contribute to their empowerment, or the absence of these factors that then have the potential to disempower them. It considers the way the students themselves see both the protective and risk elements in their lives, and how they deal with stigma, school, and identity as a person living with HIV/AIDS. The data in this work is collected through semi-structured interviews with sixteen adolescent students living in Katakwi. These sixteen students, a mixture of males and females, have varying levels of openness about discussing their HIV status. Additional interviews conducted with teachers, parents, and health care workers connected to students with HIV/AIDS creates a total of 25 participants. The diversity of stories within the voices of these sixteen students makes it clear that this unique demographic is not a homogenous population, and the levels of empowerment vary based on gender, family support, means of infection, faith in God, relationships with peers and teachers, and age. While inconsistencies exist, school is a place these students want to be despite financial struggles regarding school fees, and the risk factors that exist within the schools themselves. Despite the various factors that work against these students’ empowerment, the teenagers manage to find ways to succeed and maintain hope for futures that include education, careers and families.